Global and local contexts: the Northern Ogoja Leprosy Scheme, Nigeria, 1945-1960 - Manton John (História, Ciências, Saúde: Manguinhos, 2003)
Deriving funding from missionary sources in Ireland, Britain and the USA, and from international leprosy relief organizations such as the British Empire Leprosy Relief Association (BELRA) and drawing on developing capacities in international public health under the auspices of WHO and UNICEF through the 1950s, the Roman Catholic Mission Ogoja Leprosy Scheme applied international expertise at a local level with ever-increasing success and coverage. This paper supplements the presentation of a successful leprosy control programme in missionary narratives with an appreciation of how international medical politics shaped the parameters of success and the development of therapeutic understanding in the late colonial period in Nigeria.